Droop Compensated CIC Decimation Filter With Improved Performance - Kaur, Gaganjot (My University, 2016)
To fulfill the ever increasing demand of modern electronic devices operating at the different sampling rates, the interest has touched its zenith in the up-sampling based discrete-time signal processing techniques, which can be incorporated by using the efficient digital interpolators and decimators. From the acquired results, it is evident that the CIC filters are efficient for the low cost applications because the multipliers are not required in its implementation. However, the pass-band droop present in the CIC filters confine the scope of its practical applications. By employing compensation and multi-stage techniques, the response of CIC filter in the pass-band can be significantly improved, but at the cost of escalated hardware requirement and the computational complexity. By employing different techniques the response of filters in passband is considerably improved. And various other sharpening techniques are present to improve filter passband response.The main aim of this work is to improve the magnitude response of CIC filters and also solve the passband droop problem. For improving the passband and the transition band features of the CIC filter and for improving the performance of CIC filter there are many techniques such as compensation filter cascaded with CIC filter, sharpening technique, poly phase decimation FIR filter to achieve wide broadband compensation of the CIC filter and maximally-flat based compensator filter. The droop can be reduced by modifying the original CIC structure or by connecting an additional filter called CIC compensator in cascade with the CIC decimator. The former approach is based on a technique called sharpening. In recent years, several methods for the design of CIC compensators have been developed and now compensation is combined with a sharpening technique. In this dissertation, firstly we implemented the CIC with two stage architecture which consist of comb based decimator and sharpened comb decimator in cascade. With this sharpened section operates at lower rate by decimation factor of second stage thus reducing the number of computation and making the filter simpler than previous one and we also studied another technique which improves the response of comb filter in stopband region by changing the position of zeros means optimally rotating the zeros the zeros to place in stopband in such a way that stopband gets broader. Then based on this technique is new technique called sharpened Modified Comb filter(SMCF) which uses sharpening for passband improvement and rotated zeroes technique for stopband improvement. Also studied Compensation techniques which is also a passband improvement technique on which the very recent research in CIC area is based. After that we proposed a new Compensated CIC decimation filter with improved response which is a cascade of Sharpened Modified Comb Filter by Laddomada and the Compensation techniques, both sine based and maximally flat compensation. So by using these techniques in cascade the passband response become more flat and the stopband response is wider than conventional CIC. Later, we compared the results of new design with already existing techniques and found that results are much better than earlier ones. So overall flat passband and wider stopband is achieved with this new compensated sharpened modified comb filter.
Master of Engineering-Wireless Communication
Keywords: CIC; filter; Droop; decimation; SMCF; Compensation; Passband; Stopband